2020
DOI: 10.5344/ajev.2020.20008
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Spotted-Wing Drosophila Injury and Associated Increases in Acetic Acid in Minnesota Winegrapes

Abstract: Acknowledgments: The authors thank Adam Toninato, Sarah Holle, and Izzy Bur (UMN Fruit & Vegetable lab) for assistance with data collection and treatment applications. A special thanks to John and Jenny Thull and Drew Horton (UMN Horticultural Research Center) for sharing their knowledge and expertise in winegrapes and assisting with data collection and trial processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Once the 5–7 clusters of grapes arrived at the enology lab, the same day as harvest, they were juiced, utilizing methods similar to Ebbenga et al ( 25 ). The juicing process consisted of placing the clusters from each plot in a 1-gallon Ziploc ® bag (S.C. Johnson & Son, inc., Racine, WI), and crushed by hand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the 5–7 clusters of grapes arrived at the enology lab, the same day as harvest, they were juiced, utilizing methods similar to Ebbenga et al ( 25 ). The juicing process consisted of placing the clusters from each plot in a 1-gallon Ziploc ® bag (S.C. Johnson & Son, inc., Racine, WI), and crushed by hand.…”
Section: Methodsmentioning
confidence: 99%
“…Once crushed, the subsequent juice was poured and pressed through a stainless-steel China Cap Strainer (New Star Foodservice, Chino, CA). The resulting juice was collected in a Falcon 50 ml Conical Centrifuge Tube (Fisher Scientific, Hampton, NH) and used to measure pH, and titratable acidity ( 25 ). In 2021, a second vial of juice was collected, labeled, and stored in a freezer at −62°C until the samples were delivered via overnight express shipment to the ETS laboratories (St. Helena, CA) to obtain measurements of tannin, polymeric anthocyanins, total anthocyanins, and polymeric anthocyanins/tannin index.…”
Section: Methodsmentioning
confidence: 99%
“…Spotted-wing drosophila is highly polyphagous and is documented to feed on over 25 different plant families, including many economically-important berry and stone fruit varieties ( 15 ). Losses can be caused by direct injury to the fruit or by other indirect effects, such as reductions in wine quality based on the spread of Acetobactor bacteria to wine grapes by SWD ( 16 ). In Minnesota raspberries alone, SWD is estimated to cause more than $2 million in annual losses ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…), cultivars with higher sugar and lower acidity were more susceptible to SWD infestation (Ioriatti et al 2015). In contrast, Ebbenga et al (2021) observed successful SWD larval establishment in only six of the 34 cold-hardy grape varieties assessed in Minnesota, with some having less than 1% of berries infested. The diversity of SWD infestation results among highbush blueberries, tart cherries, and grapes suggests that there are differences among other fruit crops as well.…”
mentioning
confidence: 86%